Rejeitos radioativos gerados na produção de Mo-99 por fissão nuclear - Goro Hiromoto; José Claudio Dellamano (Brazilian Journal of Radiation Sciences)
The Brazilian Government intends to construct a facility for molibdenium-99 production by nuclear fission, among other installations, at the Brazilian Multipurpose Reactor enterprise. This study aims to investigate in which extension the activity of the radioactive waste generated in the process is enhanced if different mass of the U-235 and irradiation time of the target is employed to produce the same quantity of Mo-99. The simulation was conducted using the computational code Origen S®, assuming that the target is composed of UAlx alloy with 19.9% enriched U-235 and irradiated in a thermal neutron flux of 1x1014 n.cm-2.s-1, to produce 185 TBq of Mo-99 per week. The results obtained for 3 to 21 days of continuous irradiation of targets with different mass of U-235 show that the amount of radioactive waste generated, in terms of total activity, does not appear to be a dominant aspect to be considered in the choice of Mo-99 production parameters.